O przyszłości integracji Europie - z polskiej perspektywy - Pancer-Cybulska, Ewa (About the future of integration in Europe - Polish view, 2006)
The prospects of European integration has changed after the latest EU enlargement in 2004. The present EU members (net-payers to EU budget, especially) are trying to introduce radical changes in the budget perspective 2007-2013. Hence, there is a lot of uncertainties concerning the possibilities (opportunities) of further integration. The regional policy on the national and regional level must be enforced, while the common expenditure in this area decreased. The EU cohesion policy, directed towards economic growth and employment, should be used on the local and regional level as the main instrument of realizing the Lisbon strategy (in the perspective 2007-2013).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 110-121